Association between body fat distribution and B-lymphocyte subsets in peripheral blood - Prechtl, Pia; Schmitz, Timo; Pochert, Nicole; Traidl-Hoffmann, Claudia; Linseisen, Jakob; Meisinger, Christa; Freuer, Dennis (Immunity & ageing, 2023)
Background Obesity is associated with chronic low-grade inflammation, which is underpinned by the presence of elevated levels of circulating proinflammatory cytokines in obese individuals. Due to the close relationship between adipose tissue and the immune system, it can be speculated that the accumulation of fat may influence the frequency and phenotype of lymphocyte populations. The aim of our study was to investigate whether body fat distribution is associated with B lymphocyte composition in peripheral blood. We examined the association between visceral (VAT) and total body fat (TBF) and the frequencies of B-cell subsets in 238 subjects over a period of up to one year using random intercept models. B lymphocyte subsets were determined by fluorescence-based flow cytometry. Results Inverse associations were found between body fat measurements and plasma blasts, memory B cells, and IgM.sup.-IgD.sup.- cells. VAT, but not TBF, was positively associated with naive CD19 cells. In our analyses, both VAT and TBF showed positive associations with IgD only B cells. Conclusions In conclusion, body fat accumulation seems to be associated with a lower proportion of antibody-secreting plasma blasts and memory cells and an increasing amount of partially anergic, naive CD19 cells. Keywords: Visceral fat, Adaptive immunity, B cells, B-lymphocytes, Immune system, Obesity